Pre-Treatment with Curcumin Ameliorates Cisplatin-Induced Kidney Damage by Suppressing Kidney Inflammation and Apoptosis in Rats - Soetikno, Vivian; Sari, Shinta Dewi Permata; Ul Maknun, Lulu; Sumbung, Nielda Kezia; Rahmi, Deliana Nur Ihsani; Pandhita, Bashar Adi Wahyu; Louisa, Melva; Estuningtyas, Ari (Drug Research, 2019)
Objective In addition to oxidative stress, inflammation and apoptosis have an important role in the pathogenesis of cisplatin-induced kidney damage. This study aimed to investigate the molecular mechanisms of protective effects of curcumin against cisplatin-induced kidney inflammation and apoptosis in rats.Materials and Methods Eighteen rats were equally divided into three groups; normal (0.5% CMC-Na), cisplatin (CDPP) (7 mg/kg i.p.), and cisplatin+curcumin (CMN100) groups. Curcumin was given at a dose of 100 mg/kg orally for nine days, starts one week before giving a single dose of cisplatin. Kidney and plasma were taken for analysis.Results Cisplatin challenged rats demonstrated kidney injury as shown by reduced creatinine clearance, increased of plasma BUN, plasma creatinine, and kidney MDA, decreased of kidney GSH levels, and kidney histopathology alterations. Also, cisplatin increased ERK1/2 phosphorylation and NF-κB expression, which subsequently increased mRNA expression of TNF-α, IL-6, KIM-1, NGAL, and Bax/Bcl-2 ratio as well as decreased mRNA expression of IL-10 in kidney tissues. Pre-treatment with curcumin significantly ameliorated inflammation and apoptosis induced by cisplatin. In addition, curcumin downregulated Ctr1 and OCT2 drug transporters as compared to cisplatin group. Histopathological examination furthers confirmed the kidney damage protection effect of curcumin.Conclusions These data indicate that curcumin has nephroprotective properties against cisplatin-induced kidney damage in rats and this effect is associated with its anti-inflammatory and anti-apoptosis profiles, in addition to its antioxidant. Hence, curcumin may be useful for preventing kidney damage against cisplatin administration.
Keywords: apoptosis; inflammation; renal pharmacology